2015
DOI: 10.15517/pensarmov.v13i2.19246
|View full text |Cite
|
Sign up to set email alerts
|

Comportamiento neuromuscular posterior a la competencia en jugadores profesionales de fútbol de Costa Rica: un seguimiento tensiomiográfico

Abstract: RESUMENRojas Valverde D.; Gutiérrez Vargas, R.; Sánchez Ureña, B.; Gutiérrez Vargas, J.C.; Cruz Fuentes, I., y Salas Cabrera, J. (2015). Investigación Descriptiva Correlacional o Cualitativa. Comportamiento neuromuscular posterior a la competencia en jugadores profesionales de fútbol de Costa Rica un seguimiento tensiomiografico. PENSAR EN MOVIMIENTO: Revista de Ciencias del Ejercicio y la Salud, 13(2), 1-15. Objetivo del estudio: describir el comportamiento neuromuscular posterior a la competencia en jugadore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…TMG has been used in different studies to evaluate the morpho-functional response of muscle fibers to electrical stimuli, training (Rusu et al, 2013), clinical diagnoses (Seijas et al, 2016), risk factor for knee injuries (Alentorn-Geli et al, 2015), description, and comparison of the dominance sides of different muscle groups involved in soccer (Rojas-Valverde et al, 2018) at different times of the season (Rojas-Valverde et al, 2015). e present study described tensiomyographic values in different categories of soccer, obtaining similar average values or below those reported for the rectus femoris (Rusu et al, 2013).…”
Section: Body Composition Descriptive Values According To Experimenta...supporting
confidence: 57%
See 1 more Smart Citation
“…TMG has been used in different studies to evaluate the morpho-functional response of muscle fibers to electrical stimuli, training (Rusu et al, 2013), clinical diagnoses (Seijas et al, 2016), risk factor for knee injuries (Alentorn-Geli et al, 2015), description, and comparison of the dominance sides of different muscle groups involved in soccer (Rojas-Valverde et al, 2018) at different times of the season (Rojas-Valverde et al, 2015). e present study described tensiomyographic values in different categories of soccer, obtaining similar average values or below those reported for the rectus femoris (Rusu et al, 2013).…”
Section: Body Composition Descriptive Values According To Experimenta...supporting
confidence: 57%
“…Indeed, other studies have found no differences in TMG parameters based on players category (Rojas-Valverde et al, 2018). e muscle coupling could be similar between professional soccer players, despite they morphological and anthropometric characteristics; this is why some narrow difference could not be present among players of similar ages (Rojas-Valverde et al, 2015).…”
Section: Body Composition Descriptive Values According To Experimenta...mentioning
confidence: 84%